SHMT2 modulates the transcriptome and metabolism profiles to promote the tumor phenotypes of bladder cancer HT-1376 cells - Guo, Xiaobo; Li, Gang (Frontiers in Genetics, 2025)
IntroductionBladder cancer (BLCA) is a common malignant tumor of the urinary system. The development and progression of BLCA are controlled by multiple regulatory molecules, which have not been widely investigated.MethodsIn this study, we explored the functions and downstream targets of serine hydroxy methyltransferase 2 (SHMT2) by silencing its expression using small interference RNA (siSHMT2) in HT-1376 cells. Whole transcriptome and metabolism profiles were deeply analyzed to identify the molecular targets of SHMT2.ResultsWe found that siSHMT2 significantly reduced the proliferation rate and altered the cell cycle stages of HT-1376 cells. Moreover, siSHMT2 can modulate the expression of hundreds of genes (DEGs), including 126 upregulated and 106 downregulated DEGs. We then found that the most significant DEGs were tightly associated with progression of cancers, including PTMA, HNRNPR, RAPH1, TRAF3IP1, CNBP, and PRR15. At the same time, the alternative splicing profile was also regulated by siSHMT2, including the skipped exon as the dominant AS types. Then we confirmed the changed expression levels of PTMA, HNRNPR, RAPH1, and CNBP, and AS level of MDM2 by RT-qPCR. Finally, we identified the differential metabolites (DMs), and found the metabolism profile was significantly regulated by siSHMT2. Besides the purine metabolism, we observed that valine, leucine and isoleucine biosynthesis and degradation, TCA cycle, and propanoate metabolism were among the top pathways of DMs.DiscussionIn summary, we highlight the important roles of SHMT2 in HT-1376 cells and identified its downstream molecular targets, which are associated with the development of BLCA and can be used as therapeutic targets of BLCA in future.